Spared Nerve Injury Increases the Expression of Microglia M1 Markers in the Prefrontal Cortex of Rats and Provokes Depression-Like Behaviors - Xu, Ning; Tang, Xiao-Hui; Pan, Wei; Xie, Ze-Min; Zhang, Guang-Fen; Ji, Mu-Huo; Yang, Jian-Jun; Zhou, Mai-Tao; Zhou, Zhi-Qiang (Frontiers in Neuroscience, 2017)
Pain and depression are frequently co-existent in clinical practice, yet the underlying mechanisms remain largely to be determined. Microglia activation and subsequent pro-inflammatory responses play a crucial role in the development of neuropathic pain and depression. The process of microglia polarization to the pro-inflammatory M1 or anti-inflammatory M2 phenotypes often occurs during neuroinflammation. However, it remains unclear whether M1/M2 microglia polarization is involved in the neuropathic pain induced by spared nerve injury (SNI). In the present study, the mechanical withdrawal threshold, forced swim test, sucrose preference test, and open field test were performed. The levels of M1 markers, including ionized calcium-binding adaptor molecule 1 (Iba1), cluster of differentiation 11b (CD11b), CD68, inducible nitric oxide synthase (iNOS), interleukin-1β (IL-1β), IL-6, tumor necrosis factor-a (TNF-α), 8-hydroxy-2-deoxyguanosine (8-OH-dG), and M2 markers including CD206, arginase 1 (Arg1), IL-4 in the prefrontal cortex were determined on day 14 after SNI. The results showed that SNI produced mechanical allodynia and depressive-like behaviors, and also increased the expressions of microglia markers (Iba1, CD11b) and M1 markers (CD68, iNOS, IL-1β, TNF-α, and 8-OH-dG) in the prefrontal cortex. Notably, minocycline administration reversed these abnormalities. In addition, minocycline also promoted M2 microglia polarization as evidenced by up-regulation of CD206 and Arg1. In conclusion, data from our study suggest that SNI can lead to depression-like behaviors, while M1 polarization and consequent overproduction of pro-inflammatory cytokines plays a key role in the pathogenesis of neuropathic pain. The data furthermore indicate that modulation of inflammation by inhibition of M1 polarization could be a strategy for treatment of neuropathic pain, and might prevent the induction of neuropathic pain-induced depression symptoms.